A Novel Approach For Authorized Deduplication (International Journal of Engineering and Computer Science, 2015)
: Now a day’s data deduplication is one of the relevant data compression techniques for removing duplicate copies of repeatingdata, and has been broadly used in cloud storage to reduce the amount of storage space and save bandwidth. To defend the privacy ofsensitive data while supporting unrepeatable, the convergent encryption procedure has been suggested to encrypt the data beforeoutsourcing. To well protect data confidence, first attempt to officially address the problem of authorized data deduplication. Dissimilarfrom out-of-date deduplication organizations, the variance rights of users are further considered in duplicate check besides the data itself.We also present some new deduplication constructions supporting authorized duplicate check in hybrid cloud architecture. Security analysisproves that our scheme is secure in terms of the definitions indicated in the proposed security model. As evidence, implementation containsa prototype of our proposed authorized duplicate check scheme and conduct tested experiments using our prototype. System show that oursuggested legal replacement check scheme acquires minimal overhead compared to normal operations.